Pengendalian Dokumen Impor : Sebuah Upaya Mencegah Keterlambatan Penyelesaian Proyek kapal di PT PAL Indonesia (Persero) Surabaya - R.A.J Susilo Hadi Wibowo; Mashudi Rofiq; Dimas Pratama; Prapti Utami (Politeknik Ilmu Pelayaran Semarang, 2020)
National defense specifically for the marine dimension has the task of upholding sovereignty and maintaining the territorial integrity of the Republic of Indonesia. So that it takes a large number of warships of the Republic of Indonesia. Which are procured through domestic and foreign projects. Specifically for foreign ship procurement projects, the government through Law Number 16 of 2012 concerning the Defense Industry seeks to maximize the use of domestic production to empower the domestic defense industry and improve the welfare of the national economy. This research seeks to examine the process of handling Import documents in PT PAL Surabaya so that the completion of the project at PT PAL Surabaya is not hampered. Descriptive qualitative methods and samples were taken at PT PAL Surabaya. From the research results, it can be concluded: PT PAL Indonesia to complete its customs clearance in the customs area is not optimal. There needs to be supervision so that it can run as planned. The SP-1 issued by the Ministry of Health has been issued for a long time. So that it raises the burden of high storage and demurrage costs, to avoid it PT PAL submits Eigen-losing approval to KPPBC according to the Eigen-losing procedure, including the timeframe for hoarding, and responsibility for import duties as well as demurrage and storage costs. hampered shipbuilding production is not according to the planned target.